Notes on (1) A Drinking-cup Urn found at Bathgate; (2) the Exploration of the Floor of a Pre-historic Hut in Tiree; and (3) a Group of (at least) Sixteen Cinerary Urns found, with objects of Vitreous Paste and of Gold, in a Cairn at Stevenston, Ayrshire - Mann, Ludovic McLellan (Proceedings of the Society of Antiquaries of Scotland, 1906)